Uncertainty of shear resistance models: Influence of recycled concrete aggregate on beams with and without shear reinforcement. (1st February 2020) - Pacheco, João Nuno; de Brito, Jorge; Chastre, Carlos; Evangelista, Luís
Highlights: Influence of recycled aggregates on the model uncertainty of beams with and without stirrups. Recycled aggregate incorporation may result in unsafe designs. Resistance models that explicitly account for aggregate interlock are more affected. Probability distribution of the model uncertainty of recycled concrete beams without stirrups. Preliminary partial factor for shear design of elements without transverse reinforcement. Abstract: The model uncertainty of the shear resistance equations of three design codes {the current Eurocode 2 (2004), Model Code (2010), and the final draft of the Eurocode 2 (2020)} was investigated for coarse natural and recycled aggregate concrete beams. Databases of beams with and without shear reinforcement were made with clearly defined criteria. The statistics of the model uncertainty of natural and recycled concrete beams were compared and it was found that recycled aggregate incorporation has detrimental effects on the model uncertainty of shear design. Surprisingly, recycled concrete aggregate beams designed following the current version of Eurocode 2 (2004) are safer than those designed using the other codes. This is due to the shear resistance equations of the latter overestimating the aggregate interlock of recycled aggregate. A preliminary partial factor was proposed, offsetting the influence of recycled aggregate on the safety of beam designs. The database of beams with shear reinforcement lacks representativeness but hinted that recycled aggregate incorporation also reduces the safety of this type of shear design. The paper finishes presenting suggestions of experiments that would complement the current knowledge on this topic.